DIGITAL CITIZENSHIP SAFETY AMONG CHILDREN AND ADOLESCENTS IN INDONESIA - Gati Gayatri; Udi Rusadi; Siti Meiningsih; Dede Mahmudah; Diana Sari; nfn Kautsarina; nfn Karman (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
The study on Digital Citizenship Safety among Children and Adolescents in Indonesia aims to provide vital knowledge on how children and adolescents in Indonesia use social media and digital technology, and why they use those communication channels as well as the potential risks they might face in doing so. The data collection process of the policy research had been carried out in two years, from 2011 to 2012. Results of the study are expected to guide future policies to protect the rights of children to access information and, and at the same time, to share information and express their views or ideas in digital safety. For this, a randomized sample of children and adolescents aged 10-19 (400 in total) was taken spread across the country and spanning a mixture of urban and rural areas. The study finds that social and digital media use is an integral and growing part of the everyday life of young Indonesians. Almost all of the children and adolescents surveyed know about the Internet and most of them are Internet users. For those who are not Internet users, the number is very small. the most common reasons given are that they do not have the equipment or infrastructure to access the Internet or that they are forbidden by their parents to do so. Children and adolescents tend to use personal computers to access internet at internet cafes/vendors and school computer laboratories; laptops at home; and – above all – mobile phones or smartphones during their daily activities. They have three key motivations to access the Internet: to seek information, to connect to friends (old and new) and to be entertained. Their search for information is often driven by school assignments, while their use of social media and entertainment content is driven by their personal preference. The vast majority of their communication is with their peers, followed by their teachers, and that their communication with family members on the Internet is fairly insignificant.Keywords: Adolescent, Children, Digital citizenship, Digital media